Penyelesaian Tindak Pidana Penganiayaan Melalui Hukum Pidana Adat Di Kecamatan Koto Baru Kota Sungai Penuh Provinsi Jambi - Dinata, Arifwan Fatwa; Nelwitis; Elda, Edita (Fakultas Hukum Universitas Andalas, 2024)
The criminal act of persecution is a criminal act that affects a person's body, namely the act of injuring. One of the resolutions of the criminal act of persecution is through customary criminal law. This happened in Koto Baru District, Sungai Penuh City, the criminal act of persecution can be resolved through the applicable customary criminal law. The problems in this study are how the process of resolving criminal acts of persecution through customary criminal law in Koto Baru District, Sungai Penuh City, what are the obstacles in the application of customary criminal sanctions in Koto Baru District, Sungai Penuh City, how are efforts made to overcome obstacles in the application of customary criminal sanctions in Koto Baru District, Sungai Penuh City. This research uses sociological juridical methods and descriptive research. Based on the research conducted, the results of the process of solving criminal acts of persecution through customary criminal law in Koto Baru District, Sungai Penuh City, were obtained in a bajenjeng naeak batakah tuhang. Obstacles in the application of customary criminal sanctions include legal rule factors, law enforcement factors, legal culture factors, and economic factors. Efforts were made to overcome obstacles where customary administrators held seminars and customary dialogues. Traditional managers give instructions to traditional leaders in solving cases objectively and professionally. A traditional proverb asserts dimanao bumui dipijiak disitu langangk dijunjio to foster public legal awareness. If the offender cannot fulfill customary criminal sanctions on his own, he can ask his family for help